Pre-Procedural Anxiety and Associated Factors Among Women Seeking for Cervical Cancer Screening Services in Shenzhen, China: Does Past Screening Experience Matter? - Lin, Wei; Huang, Weikang; Mei, Chaofan; Zhong, Chuyan; Zhu, Leilei; Liu, Peiyi; Yuan, Shixin; Liu, Zhihua; Wang, Yueyun (Frontiers in Oncology, 2022)
Background Research gaps exist in addressing the psychological harm related to the cervical cancer screening. Anxiety is the most common distress driven by the screening procedures, which may be affected by past screening experience (PSE) but with uncertainty. This study aimed to evaluate the pre-procedural anxiety in cervical cancer screening and to identify the influence attributed to PSE. Methods A cross-sectional survey targeted women seeking for cervical cancer screening services was conducted from June 5th to December 31st, 2020 in Shenzhen. The 20-item state anxiety scale of the State-Trait Anxiety Inventory (STAI-S) was applied to measure pre-procedural anxiety, in which a score of 40 or higher was regarded with anxiety symptoms. Logistic regression models were established to explore potential associated factors of pre-procedural anxiety both for women with and without PSE. Results Overall, 3,651 women were enrolled, in which 36.1% had never been screened and the remaining 63.9% had been screened at least once before. Women without PSE demonstrated more prevalent pre-procedural anxiety (74.5% vs. 67.8%, P ＜0.001) than their experienced counterparts. Among women without PSE, having heard of cervical cancer screening was associated with a lower likelihood of pre-procedural anxiety (OR: 0.37, 95%CI: 0.25~0.56). Among experienced women, participating three or more times screening was negatively associated with anxiety symptom (OR: 0.67, 95%CI: 0.53~0.84), however, both receiving screening within three years (OR: 1.58, 95%CI: 1.27~1.97) and unknowing previous screening results (OR: 1.42, 95%CI: 1.11~1.82) increased the susceptibility of pre-procedural anxiety. Conclusions Women participating in cervical cancer screening commonly present pre-procedural anxiety. The association between PSE and pre-procedural anxiety may be influenced by past screening times, interval, and results. Psychological counseling according to women’s PSE before cervical cancer screening is warranted of necessity.